INFLUENCE OF SELF-DEVELOPMENT ON POSITIVE BODY IMAGE AND LEADERSHIP STYLE AMONG TRAINEE COUNSELLOR IN HIGHER INSTITUTION - Anis Nurshafiqah, Azhar (UNIMAS, 2022)
The purpose of this study was to investigate the influence of self-development on positive body image and leadership style among trainee counsellor in higher institutions, Universiti Pendidikan Sultan Idris (UPSI), Universiti Putra Malaysia (UPM) and Universiti Utara Malaysia (UUM). A correlational research design was adopted in this study to address the research objectives. There were one-hundred and twenty (120) participants among Bachelor in Counselling with Honours students who participated in this research. About seven sets of questionnaires used in this study: Section A: Demography Question, Section B: Experience in Close Relationship (ECR). Section C: Rosenberg Self-Esteem Scale (RSE), Section D: Counselling Self-Estimate Inventory (COSE), Section E: Life-Orientation Test- Revised (LOT-R), Section F: Body Image Quality of Life Inventory (BIQLI) and Section G: Multifactor Leadership Questionnaire (MLQ) Form 6S. The results of the study were analysed using Pearson Product Moment Coefficient and Multiple Regression. This research indicated there was no significant relationship of self-development (attachment style, self-esteem, self-efficacy and optimism) between positive body image and leadership style. Based on the Pearson Product Moment Coefficient analysis, only three sub-variables; attachment style, self-esteem and optimism showed there is a significant relationship on positive body image. While for self-efficacy, there is no significant relationship between self-efficacy and positive body image. However, all sub-variables showed a significant relationship on leadership style. For Multiple regression analyses reported only three sub-variables of self-development; attachment style, self-esteem and optimism have a significant influence on positive body image. Meanwhile, four sub-variables showed significant influence on leadership style. In conclusion, the implications of the research were divided into two categories; theoretical and practical implication. In term of theoretical implication, the underlying could explained the role of self-development between positive body image and leadership style as the elements of counsellor. This research provided practical implication in which the counsellor could be more aware on development of self, view positive in body image and be a good leader in leading a counselling. Future researcher are recommended to (1) expand more involved variables (2) include more respondents (3) choose appropriate instruments (4) consider qualitative research.